2022
DOI: 10.3389/fendo.2022.915394
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trajectories of BMI and cumulative incident metabolic syndrome: A cohort study

Abstract: BackgroundBody mass index (BMI) has been widely recognized as a risk factor for metabolic syndrome (MetS). However, the relationship between the trajectory of BMI and cumulative incident MetS is still unclear. We investigate the associations of long-term measurements of BMI with MetS among young adults in the China Health and Nutrition Survey.MethodsWe enrolled individuals aged 10 to 20 at baseline with recorded BMI at each follow-up interview, and 554 participants were finally included in our study. The asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Several other studies with the same approach, utilizing latent class modeling, reached different numbers of WC and BMI trajectory groups, which were labeled to the pattern of dynamic changes and ranged from two to 6 groups, in different studies. (25,26,(35)(36)(37)(38)(39) Also, the same number of BMI trajectory groups in our study was de ned in some previous studies with the follow-up of subjects from childhood to adulthood. (25,36,37,39) Childhood overweight/ obesity is de ned to be a major risk factor for adulthood obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other studies with the same approach, utilizing latent class modeling, reached different numbers of WC and BMI trajectory groups, which were labeled to the pattern of dynamic changes and ranged from two to 6 groups, in different studies. (25,26,(35)(36)(37)(38)(39) Also, the same number of BMI trajectory groups in our study was de ned in some previous studies with the follow-up of subjects from childhood to adulthood. (25,36,37,39) Childhood overweight/ obesity is de ned to be a major risk factor for adulthood obesity.…”
Section: Discussionmentioning
confidence: 99%
“…(25,26,(35)(36)(37)(38)(39) Also, the same number of BMI trajectory groups in our study was de ned in some previous studies with the follow-up of subjects from childhood to adulthood. (25,36,37,39) Childhood overweight/ obesity is de ned to be a major risk factor for adulthood obesity. The results of a systematic review study by Singh et al (6) showed that overweight and obese youth have an increased risk of being overweight during adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analytical approach is especially vital in the context of MetS, given that the condition's severity and characteristics can fluctuate over time, potentially altering an individual's risk profile for serious ailments like heart disease, stroke, and type 2 diabetes. [5][6][7] By employing trajectory analysis, researchers gain the ability to not only monitor the dynamic progression of MetS but also to pinpoint specific patterns and shifts in its componentssuch as blood pressure, blood sugar levels, waist circumference, and lipid profiles. This enriched understanding enables a more nuanced comprehension of how transitions between metabolically healthy and unhealthy states influence the development and progression of related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…MetS in children and adolescents can be diagnosed using a variety of techniques. The International Diabetes Federation (IDF) states that MetS is diagnosed in children between the ages of 10 and 16 who have central obesity (90th percentile or higher), triglycerides (TG) of 150 mg/dl or higher, HDL-C of 40 mg/dl or higher, systolic or diastolic blood pressure (BP), fasting plasma glucose (FG) of 100 mg/dl, or a history of type 2 diabetes (Aditama et al, 2021;Ying et al, 2022). According to WHO guidelines, MetS is diagnosed when three or more of the following characteristics are present: BMI > 95th percentile, hyperinsulinemia, impaired fasting glucose, or impaired glucose tolerance, BP > 95th percentile, TG > 105/136 mg/dL (1.2/1.5 mmol/L) for children > 10 years old, and HDL-C > 35 mg/dL (0.9 mmol/L) (Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%